The numerical assessment of motion strategies for integrated linear motor during starting of a free-piston engine generator - Mohd Razali, Hanipah; A. R., Razali (IOP Publishing Ltd, 2017)
Free-piston engine generator (FPEG) provides a novel method for electrical power generation in hybrid electric vehicle applications with scarcely reported prototype development and testing. This paper is looking into the motion control strategy for motoring the FPEG during starting. There are two motion profiles investigated namely, trapezoidal velocity and Scurve velocity. Both motion profiles were investigated numerically and the results have shown that the S-curve motion can only achieve 80% of the stroke when operated at the proposed motoring speed of 10Hz.